pysubgroup: Easy-to-Use Subgroup Discovery in Python - Lemmerich, Florian; Becker, Martin (Machine Learning and Knowledge Discovery in Databases, 2019)
This paper introduces the pysubgroup package for subgroup discovery in Python. Subgroup discovery is a well-established data mining task that aims at identifying describable subsets in the data that show an interesting distribution with respect to a certain target concept. The presented package provides an easy-to-use, compact and extensible implementation of state-of-the-art mining algorithms, interestingness measures, and visualizations. Since it builds directly on the established pandas data analysis library—a de-facto standard for data science in Python—it seamlessly integrates into preprocessing and exploratory data analysis steps. Code related to this paper is available at: http://florian.lemmerich.net/pysubgroup.